2023
DOI: 10.1021/acs.chemmater.3c01348
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Sulfur-Sensitization of PtNi Nanoalloy for Efficient Electrocatalytic Hydrogen Production in Alkaline Simulated Seawater

Fei Yu,
Yu-Xuan Xiao,
Jiang-Bo Chen
et al.

Abstract: Optimization of the electronic structure and surface physicochemical properties of PtNi nanoalloys by incorporation of sulfur (S) is an effective strategy for improving the efficiency of the electrocatalytic hydrogen evolution reaction (HER). However, few studies have been carried out to assess the seawater electrocatalytic performance of PtNi by incorporation of interfacial S from CdS nanocrystals. In this study, a simple method is developed to prepare CdS/PtNi, composed of a PtNi alloy supported with CdS qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…PtNi alloy nanoparticles are interesting candidates for reducing the amount of Pt in HER catalysts as PtNi/C nanoparticles have been reported to outperform the HER activity of Pt/C benchmark under alkaline conditions [31][32][33]. The incorporation of sulphur to PtNi nanoalloys can enhance HER activity and durability of PtNi catalyst in alkaline seawater [34]. In addition, PtNi alloy nanoparticles have been shown to increase the catalytic activity in oxygen reduction reactions (ORRs) compared to pure platinum [35][36][37], and PtNi clusters have been reported to be highly efficient catalysts for methane dehydrogenation [38].…”
Section: Introductionmentioning
confidence: 99%
“…PtNi alloy nanoparticles are interesting candidates for reducing the amount of Pt in HER catalysts as PtNi/C nanoparticles have been reported to outperform the HER activity of Pt/C benchmark under alkaline conditions [31][32][33]. The incorporation of sulphur to PtNi nanoalloys can enhance HER activity and durability of PtNi catalyst in alkaline seawater [34]. In addition, PtNi alloy nanoparticles have been shown to increase the catalytic activity in oxygen reduction reactions (ORRs) compared to pure platinum [35][36][37], and PtNi clusters have been reported to be highly efficient catalysts for methane dehydrogenation [38].…”
Section: Introductionmentioning
confidence: 99%
“…4–7 In the group investigated thus far, Pt-based materials have been found to possess superior H adsorption properties that make them the most efficient catalyst for the cathodic hydrogen evolution reaction (HER). 8–10 However, it is commonly observed that the alkaline seawater splitting performance of Pt-based catalysts is substantially lower than that in alkaline media, primarily owing to chloride ion-promoted corrosion associated with metal chloride/hydroxide formation (eqn (1)–(3)). 11–13 This highlights an urgent need for new strategies to design high-performance and durable Pt-based electrocatalysts for seawater HER.Pt + Cl − → PtCl ads + e − PtCl ads + Cl − → PtCl x − PtCl x + OH − → Pt(OH) x + Cl − …”
mentioning
confidence: 99%